Comparative review of copper-associated chronic hepatitis in dogs and Wilson disease in humans - Ullal, Tarini; Choi, Eunju April; Gui, Dorina; Medici, Valentina (Frontiers in Veterinary Science, 2025)
Copper-associated chronic hepatitis (CAH) in dogs and Wilson disease (WD) in humans are progressive hepatic disorders caused by copper accumulation. Although both diseases share similar pathomechanisms of copper-induced liver injury, they diverge in some aspects of etiology, clinical manifestations, diagnostic methods, and therapeutic strategies. Wilson disease arises from inherited ATP7B mutations while CAH in dogs might be more influenced by excess dietary copper with ATP7B mutations playing a lesser role. Dogs exhibit hepatic disease whereas humans show hepatic and/or extrahepatic manifestations, including neuropsychiatric and ocular signs. Dogs with CAH accumulate copper centrilobularly unlike human patients who develop copper periportally initially. There are several non-invasive diagnostic tools used to monitor the effect of treatment in humans with WD that are not available for dogs with CAH. Copper chelation and dietary copper restriction are used to treat dogs with CAH and humans with WD, but liver transplantation is not an option for dogs with CAH. This comparative review highlights the similarities and differences between CAH and WD, offering insights that may improve our understanding and management of copper associated liver diseases in dogs and human patients.